Agama, Konflik Sosial dan Kekerasan Politik - Nur Latifah (FONDATIA, 2018)
The emergence of social conflict and violence that uses religion as justification has become a problem that adorns the history of violence today. Social conflicts which are followed by acts of violence that use religious issues in Indonesia, certainly do not occur in empty space and apart from some socio-political phenomena that follow. Putting religion as a variant of the potential trigger of social conflict is not easy. This is so, because religion is considered a teaching that is always associated with teachings that are full of values of peace and safety. The emergence of social conflict in various regions such as, in Ambon, Mataram, Situbondo, Tasikmalaya, Regasdengklok, and other areas, selayang in view can be seen as religious conflict, but when examined more deeply cannot be separated from the role of the political elite, both at the central level and local. Likewise with the violence experienced by Ahmadiyah congregation groups, it is not too difficult to state that the area of religion has been made as a means of legitimacy and legitimacy in carrying out acts of violence. In this regard, religion has been used as a shield for violent behavior, in the interests of a group of people or an elite.